The Genetic Architecture of Chronic Mountain Sickness in Peru - Gazal, Steven; Espinoza, Jose R.; Austerlitz, Frédéric; Marchant, Dominique; Macarlupu, Jose Luis; Rodriguez, Jorge; Ju-Preciado, Hugo; Rivera-Chira, Maria; Hermine, Olivier; Leon-Velarde, Fabiola; Villafuerte, Francisco C.; Richalet, Jean-Paul; et al. (Frontiers in Genetics, 2019)
Chronic mountain sickness (CMS) is a pathological condition resulting from chronic exposure to high-altitude hypoxia. While its prevalence is high in native Andeans (>10%), little is known about the genetic architecture of this disease. Here, we performed the largest genome-wide association study (GWAS) of CMS (166 CMS patients and 146 controls living at 4,380m in Peru) to detect genetic variants associated with CMS. We highlighted four new candidate loci, including the first CMS associated variant reaching GWAS statistical significance (rs7304081; P = 4.58 x 10-9). By looking at differentially expressed genes between CMS patients and controls around these four loci, we suggested AEBP2, CAST and MCTP2 as candidate CMS causal genes. None of the candidate loci were under strong natural selection, consistent with the observation that CMS affects fitness mainly after the reproductive years. Overall, our results reveal new insights on the genetic architecture of CMS, and do not provide evidence that CMS associated variants are linked to a strong ongoing adaptation to high altitude.